Dakwah dan Pemberdayaan Masyarakat - Ansori, Teguh (Proceedings of International Conference on Da'wa and Communication, 2019)
Community empowerment is part of preaching activities, because preaching is not only limited to lectures. Empowerment of the community as a real action propaganda known as billhal propaganda. Preaching does not only improve the quality of your faith, but also preaching also needs to pay attention to the teraf of people's lives as honey. Improving the standard of living of the community can be done by means of community empowerment. In tune with the paradigm of community empowerment, that preaching has the aim to change the situation of honey through economic, social, political, cultural, educational, health and so forth. Community empowerment positions madu as both subject and object in Da'wa activities. In the Islamic perspective community empowerment has a starting goal which is to eliminate socioeconomic gaps between one another. So that Islam is taught the principles of social security, the principle of equality, the principle of participation, the principle of respect for the work ethic, and the principle of help. There are two ways taken in Islam in community empowerment, that is consumptive community empowerment and productive community empowerment.